Short-Term and Long-Term Effects of Levetiracetam Monotherapy on Homocysteine Metabolism in Children with Epilepsy: A Prospective Study - Attilakos, Achilleas (J Clin Neurol, 2019)
BACKGROUND AND PURPOSE: Long-term treatment with some older antiepileptic drugs may lead to hyperhomocysteinemia. Levetiracetam (LEV) is a newer broad-spectrum antiepileptic agent whose effects on homocysteine concentrations remain unclear. The purpose of this study was to prospectively determine the short-term and long-term effects of LEV monotherapy on homocysteine metabolism in children with epilepsy. METHODS: The study population consisted of 32 children [18 females, 14 males; age 5.94±4.10 years (mean±SD), age range 1–15 years] who received LEV monotherapy for new-onset epilepsy. Serum folate, serum vitamin B(12), and plasma total homocysteine (p-tHcy) were measured before and at 2 months (n=32), 6 months (n=25), and 12 months (n=18) of LEV monotherapy. RESULTS: p-tHcy was significantly decreased at 2 months of treatment (p=0.031). Furthermore, analysis of covariance showed statistically significant decreases in p-tHcy at 2 months (p=0.013) and 6 months (p=0.015) of LEV treatment after controlling for age, sex, body mass index, and LEV dose. There were no significant alterations in the other parameters during the study. The drug doses were 18.1±7.1, 20.1±9.2, and 21.2±11.8 mg/kg at 2, 6, and 12 months of LEV treatment, respectively. CONCLUSIONS: In contrast with older antiepileptic drugs, long-term LEV monotherapy in children with epilepsy does not cause adverse alterations on homocysteine metabolism. Larger prospective studies are needed to definitively clarify whether LEV may be considered a safer alternative drug for preventing antiepileptic-drug-induced cardiovascular complications in adult life.